BOSSONOMICS DESTRUCTIVE LEADERSHIP - Shewchuk, Muriel (Operating Room Nurses Association of Canada Journal, 2008)
IF YOU RATED YOURSELF AND THE MANAGEMENT COLLEAGUES YOU WORK WITH WHAT WOULD BE YOUR HONEST ASSESSMENT? “STAR”, “OKAY”, “JERK”, “USELESS”… or worse names? What are you called at the dinner table of your employees? How many of your employees say “I hate my job and my boss”? How hard is the door slammed when your employee arrives home? Were the children screamed at? How much crying goes on at home because of you and your colleagues? How much do you contribute to the insomnia of your staff? How much absenteeism is related to your workplace’s toxic environment?